(3JCKjQ GdfTGW GdHOfj h GdQjGVj Ydi GfJHGg JdGejP GdGbSGe GdfgGFjI ddeQMdI GdKGfhjI h YdGbJg HJMUjdge GdOQGSj s - (3gWGd, SejQs; (3HhYLfGb, ceGds; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3gPG GdHMK YHGQI OQGSI hUajI JJfGhd ehVhY GdfTGW GdHOfj GdQjGVj GdPj gh YfUQ gGe aj GdMjGI GdjhejI ddaQO HUaI YGeI h GdMjGI GdjhejI ddJdejP HUaI NGUI HMjK CffG ef NdGd gPg GdOQGSI SfMGhd GHQGR eOi JCKjQ eeGQSI eNJda GdfTGWGJ GdQjGVjI Ydi YedjI ef GdYedjGJ GdYbdjI GdgGeI dJYde GdJdejP CdG h gj YedjI GdGfJHGg h cPdc eMGhdI eYQaI YdGbI cd gPG HGdJMUjd GdOQGSj HGdfSHI ddJdGejP aj GdeQMdI GdKGfhjs
(3OcJhQGIs
Keywords: (3GdJMUjd GdOQGSjs; (3GdJYdje GdKGfhjs; (3GdfTGW GdHOfj GdQjGVjs; (3fXQjI h efgLjI GdJQHjI GdHOfjI h GdQjGVjIs